Cystoid Macular Edema Medical and Surgical Management - Schaal, Shlomit; Kaplan, Henry J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Written for comprehensive ophthalmologists and vitreoretinal surgeons, this book discusses state-of-the-art medical and surgical management of cystoid macular edema (CME) and explains the current understanding of the pathophysiology of the condition and methods of diagnosis. The management approach is clearly detailed for each potential presentation, including CME occurring in association with uveitis, diabetes mellitus, vitreoretinal interface changes, retinal vascular occlusions, and lens-induced pathology. The guidance takes full account of the continued expansion in medical treatment options due to the development of new drugs and the increased availability of minimally invasive surgical procedures. Additionally, since therapeutic approaches to CME depend on a clear understanding of pathophysiologic mechanisms and the structural changes in the vitreous and neurosensory retina revealed by imaging studies, these aspects are carefully considered as well.
PATHOPHYSIOLOGY AND DIAGNOSIS OF CME: Introduction -- Pathophysiology of CME -- Diagnosis of CME (Imaging). MEDICAL MANAGEMENT OF CME: CME Associated with Uveitis -- CME Associated with Diabetes -- CME Associated with Vitreo-Retinal Interface -- CME Associated with Retinal Vascular Occlusions -- Retained Lens Fragments in Lens Induced CME. SURGICAL MANAGEMENT OF CME: CME Associated with Uveitis -- CME Associated with Diabetes -- CME Associated with Vitreo-Retinal Interface -- CME Associated with Retinal Vascular Occlusions -- Lens Induced CME. Conclusion and Outlook Towards the Future.
Keywords: Medicine; Ophthalmology; Medicine & Public Health; Ophthalmology